2002
DOI: 10.1097/00000478-200201000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Meningioangiomatosis Occurring in a Young Male Without Neurofibromatosis

Abstract: A 16-year-old young male experienced persistent headache, and brain computed tomography and magnetic resonance imaging showed an abnormal mass with calcification in the right temporal lobe of the cerebrum. The tumor was located in the leptomeninges and cerebral cortex. In the leptomeninges, multiple calcified-fibrous nodules were noted. In this area spindle-shaped cells were arranged in a fascicular or storiform pattern. A few meningioma-like nodules were also present. With continuity of this leptomeningeal le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…2,16 The pathognomonic finding of this tumor is its invasive nature, characterized pathologically by invasive meningiovascular proliferation, perivascular cuffs of spindle cell proliferation, perivascular connective tissue proliferation, and neurofibrillary tangles, often interspersed with more discrete meningiomas (3,4,9,10,12,16–21,24,26). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,16 The pathognomonic finding of this tumor is its invasive nature, characterized pathologically by invasive meningiovascular proliferation, perivascular cuffs of spindle cell proliferation, perivascular connective tissue proliferation, and neurofibrillary tangles, often interspersed with more discrete meningiomas (3,4,9,10,12,16–21,24,26). …”
Section: Discussionmentioning
confidence: 99%
“…Sporadic meningioangiomatosis rarely occurs in children younger than 3 years of age. Anatomically, lesions are most frequently identified in the temporal lobe, followed by the frontal, parietal, and occipital lobes in descending order (4,16,21). Clinically, meningioangiomatosis usually presents with seizures and headaches.…”
Section: Discussionmentioning
confidence: 99%
“…Wiebe et al [1] reported that 43% of patients became seizure-free, and improvements in epilepsy occurred in 30% of cases; furthermore, 20% of cases did not require administration of antiepileptic drugs postoperatively. When surgical treatment failed to obtain favorable outcomes, it was suggested that the epileptic foci were extended to the adjacent cortex or even remote regions [9.] In the present case, an intraoperative electrocorticogram demonstrated epileptic discharges arising from the cortex flanking the hard mass, but not from the lesion itself.…”
Section: Discussionmentioning
confidence: 66%
“…Partial removal of the tumor has been shown to improve symptoms, but total removal still seems to be more effective [8,20]. In patients in whom postoperative seizure control was not successful, extension of the epileptic foci was found to occur with time [21]. In our patient, ECoG revealed perilesional cortical spikes, and epileptogenic foci were present in not only the right temporal lobe but also the right hippocampus.…”
Section: Discussionmentioning
confidence: 76%